The Legal Liability of the Chartmaker - Troop, Peter M. (The International Hydrographic Review, 2015)
Recent developments in the law have imposed increased liability and responsibility on Government Departments and Agencies providing services to the public. The Canadian Hydrographic Service, as the Crown Agency providing reliable information to the marine navigator, must be aware of the legal responsibilities and duties and the extent to which the Crown may be liable for shipping casualties and other marine accidents. The degree of reliance placed on charts and other nautical publications of the CHS potentially exposes the Government of Canada, under the Crown Liability Act, to claims by ship owners and cargo owners for damages ranging up to many millions of dollars based upon misleading or inaccurate charts. Members of the CHS need to be aware of this responsibility and take all necessary measures to protect and to limit this potential exposure of the Government of Canada. The importance of the CHS establishing standards of excellence and providing for mechanisms to ensure that these standards of excellence are met is emphasized. Special reference is made to the legal problems and other scientific investigations and the manner by which the Crown can discharge its responsibility and limit its liability there for. The heavy reliance by Government and the marine public on the hydrographer’s creditability and expertise is also described, as well as the use to which the information and results are put. The legal problems associated with changing technology, new procedures and the updating of older charts and publications to meet modem charting standards are reviewed and discussed.